Enhanced thermal stability of lactic acid bacteria during spray drying by intracellular accumulation of calcium. (August 2020) - Wang, Yan; Hao, Fan; Lu, Wenjie; Suo, Xiangshu; Bellenger, Elise; Fu, Nan; Jeantet, Romain; Chen, Xiao Dong
Abstract: Lactococcus lactis ssp. cremoris and Lactobacillus acidophilus NCFM were cultured in growth media supplemented with CaCl2 to induce intracellular accumulation of Ca 2+ . Both strains grown with 10 mM Ca 2+ demonstrated enhanced thermal stability, with increased survival after spray drying from 49.9% to 64.9% for the coccus and from 35.5% to 43.3% for the rod. The increased intracellular Ca 2+ level was confirmed with murexide assay. Adding Ca 2+ in the reconstitution solution could not improve the viability of spray dried cells at extended storage stages. We hypothesized that the over-presence of intracellular Ca 2+ might stimulate the activity of heat shock proteins, increasing cell survival towards heat stress. The positive effect of calcium partly explained the protective mechanism of some calcium-containing protectants. The reported approach, which improves the stress tolerance of cells, can be combined with the optimization of spray drying conditions and protectant formulation for developing a consolidated powder production scheme. Highlights: 10 mM CaCl2 was added to growth medium to induce accumulation of intracellular Ca 2+ . The resulting L. cremoris and L. acidophilus cells showed enhanced heat stability. By culturing with Ca 2+, both strains showed increased survival after spray drying. Reconstitution with Ca 2+ did not improve LAB viability for powders at storage stage. The effect of Ca 2+ was ascribed to stimulating the activity of heat shock proteins.